The exhaustion of the brazilian growth cycle - Camargo, Daniel Muniz (2013)
Much has been said about Brazil in the past decade , emphasizing how the country has risen to become one of the richest economies in the world and a global player . Nevertheless, there are signs that this recent prosperity is coming to an end , indicating that there was an excessive optimism about the country's apparent economic success and continuous growth prospects. Brazil has relied on commodity exports and on a consumption - led growth model , that became the prime movers of the economy. A booming world economy demandin g commodities and a strong and unexplored internal market help explain Brazilian growth in the past decade. However, this model has several shortcomings . Inflation is rising once again and the bottlenecks that stand in the way to economic development haven 't been solved . The aim of this dissertation is to demonstrate that the current growth cycle of the Brazilian Economy is ending. Data from various local and international sources will be used to show that the country, once again, had an ephemeral growth an d lacks an adequate economic structure that i s able to foster long term development. A brief analysis of economic fundamentals, business climate and other issues related to growth and development will be presented , a rticulat ing the data and facts to find u nderlying causes and explanations o f the current downturn.